Science Outreach at Madrasa Menggunakan Poster Fisika pada Materi Kecepatan - Pranata, Ogi Danika; Seprianto, Seprianto; Adelia, Ismi; Darwata, Siti Riva; Gusvina, Fadilla; Dewi, Mustika Sandra (Institut Agama Islam Negeri Kerinci, 2024)
This community service activity aims to implement and evaluate the effectiveness of using posters as a learning medium on the topic of velocity and to understand students' perceptions of the posters. The research method used is community-based research, involving collaboration with an existing learning community. The research subjects consisted of 16 students who participated in learning using a physics poster about the sonar system. Concept understanding data was obtained through practice exercises, and student perception data was collected using a questionnaire. Descriptive analysis results showed that students' concept understanding was high, with an average score of 82.81. Fifty percent of the students achieved the maximum score of 100. Students' perceptions of using posters were also positive, with an average score of 3.93 out of 5. Students stated that posters helped in understanding concept and made learning more engaging, although there were some difficulties in reasoning problems and mathematical calculations. The conclusion of this research indicates that using posters as a learning medium is effective in enhancing concept understanding and student engagement. These findings recommend using posters as one of the learning strategies in science teaching at schools to create an interactive and engaging learning atmosphere.